O silêncio dos aprendizes: um estudo sobre o "período silencioso prolongado" de aprendizes de língua estrangeira (inglês) - Toledo, Fabiano Bernardes de (2010)
The aim of this work was to investigate factors that could be related to the silence (in the classroom) of students of English as a foreign language at advanced levels of study, a phenomenon that we will call prolonged silence period, based on Krashen‟s silent period concept. According to this concept, it is natural that students at the beginning of the learning process of a new language go through a period in which they remain silent, just receiving linguistic input, until they have acquired some knowledge and the necessary confidence to start talking. Some students, however, tend to remain silent in class, even at higher levels of language study. In this investigation, we focus on how these students act in class. This work is based on studies about affective factors involved in the language teaching and learning process carried out by Brown (2000), Almeida Filho (1993) and Krashen & Terrell (1998), on studies about students beliefs regarding this process, carried out by Vieira-Abrahão and Barcelos (2006), Barcelos (2001) and Almeida Filho (1993), among others. The methodology of the research involves interviews, field notes, questionnaires, student´s retrospective selfevaluation, and audio and video recordings with students from two intermediateadvanced level groups and three advanced level groups of a private language institute. The goal is to identify and discuss possible factors that contribute to the lack of oral participation of these students in class, as well as their beliefs regarding the foreign language teaching and learning process, especially as it is related to oral practice. Through this work we verified, for example, the existence of a belief according to which being at an advanced level of learning of the target language means not being allowed to make mistakes, due to the thought that at this level of studies the oral production must be free from errors. Consequently, to avoid making such errors, some students opt to remain silent in class.